2022
DOI: 10.3389/fgene.2022.813216
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analysis of Long- and Short-Read Transcriptomes Identify the Regulation of Terpenoids Biosynthesis Under Shading Cultivation in Oenanthe javanica

Abstract: Water dropwort (Oenanthe javanica) is a popular vegetable with high nutritional value and distinctive flavor. The flavor is mainly correlate with the biosynthesis of terpenoids. Shading cultivation was used to improve the flavor in the production of water dropwort. However, the changes of terpenoids and the genes involved in terpenoids biosynthesis under shading treatment remains unclear. In this study, the long- and short-reads transcriptomes of water dropwort were constructed. In total, 57,743 non-redundant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…Previous studies have found that the unique aroma of water dropwort is related to the accumulation of secondary metabolites, including terpenoids, alcohols, etc. [ 7 , 9 , 60 ]. Our previous research has found that shading cultivation was used to improve the flavor in the production of water dropwort.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have found that the unique aroma of water dropwort is related to the accumulation of secondary metabolites, including terpenoids, alcohols, etc. [ 7 , 9 , 60 ]. Our previous research has found that shading cultivation was used to improve the flavor in the production of water dropwort.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous research has found that shading cultivation was used to improve the flavor in the production of water dropwort. The terpenoid biosynthesis genes were down−regulated under the shading treatment [ 9 ]. In addition, GC−MS technology was used to determine and analyze the volatile substances related to the flavor of water dropwort [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations